Survival and epidemiological, social, economic and clinical aspects of pediatric peritoneal dialysis: An integrative review - Mariana Rodrigues Ramos; Maria Goretti Moreira Guimarães Penido; Sergio Veloso Brant Pinheiro (Archives of Renal Diseases and Management - Peertechz Publications, 2022)
Introduction: The kidneys are fundamental organs for survival and the progressive loss of their functions causes the loss of regulatory, excretory and endocrine functions, essentially affecting the entire balance of the organism. Chronic Kidney Disease (CKD) is considered a complex disease and a worldwide public health problem with the number of patients continuously increasing, even in the pediatric population. CKD often progresses to end-stage requiring Renal Replacement Therapy (RRT). Kidney transplantation is the treatment of choice to maximize the survival, growth, and development of pediatric patients, however, if dialysis is necessary, Peritoneal Dialysis (PD) is a high-quality and low-cost RRT modality preferred therapy for children and adolescents with End-Stage Kidney Disease (ESKD). In this scope, this study aimed to carry out an integrative review of the survival and the epidemiological, clinical, social and economic profile of children and adolescents with PD. Methods: It is an integrative review whose data collection was carried out between January 2019 and January 2021 following the methodology suggested by the literature, using a validated data collection instrument. The following health science descriptors (DECs) from the VHL portal (virtual health library) were used: children, adolescents, chronic peritoneal dialysis, survival and epidemiology. Results: Thirty-five studies were selected and evaluated using the Critical Appraisal Skills Program (CASP). The level of evidence of the articles was assessed using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) scale. Survival and epidemiological, social, economic and clinical aspects of pediatric PD in Brazil and worldwide have been described and reviewed. Conclusions: The complexity and costs involved in the care of pediatric patients in RRT impact their survival. Mortality and morbidity are higher than in healthy children and life expectancy is considerably lower. ESKD is more severe in the pediatric population and interferes with general development, weight and height gain, regulation of mineral metabolism and causes definitive cardiovascular calcifications. Kidney transplantation is the treatment of choice to maximize the survival, growth and development of pediatric patients. However, if dialysis is necessary PD is the first-choice modality in this population. Unfortunately, data are scarce in the literature on its survival and its epidemiological, social, economic and clinical aspects.